Etnobotani Tumbuhan Pangan Tradisional Masyarakat Batak di Kabupaten Toba Sumatera Utara - Amrul, Hanifah Mutia Zaida Ningrum (Mahesa Research Center, 2025)
This study examines the diversity of plant species utilized as traditional food sources by the Batak community in Toba Regency, North Sumatra. The research aims to document traditional knowledge related to local food resources, including staple foods, vegetables, fruits, and cooking spices. Data were collected through field observations and semi-structured interviews, while the data analysis was conducted using a qualitative descriptive approach. The results revealed that the Batak people utilize 125 plant species, consisting of 13 carbohydrate sources, 37 vegetable species, 42 fruit species, and 34 plant species used as spices. The dominance of cultivated plants indicates an adaptation of the community to modern agricultural systems, while the continued use of wild plants reflects the preservation of local wisdom. This study is expected to contribute to the development of sustainable, locally based food security and to serve as a potential reference for the development of functional food products.